KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULAR PADA RHIZOSFER AREAL REVEGETASI LAHAN PASCATAMBANG EMAS PT NATARANG MINING - Siti Tisas Sitra Sanana; Ceng Asmarahman; Melya Riniarti; Duryat Duryat (Forestry Study Program University Of Mataram, 2022)
Identification of local AMF is crucial in accelerating the process of successful revegetation on post-mining land. The research objective was to identify the diversity of AMF species on PT Natarang Mining's post-mining land. Soil sampling using purposive sampling techniques in a non-proportional manner with a plot measuring 20 m x 20 m determined based on the spread of vegetation growing at the location. Sampling site on revegetation land in 2015 and 2018. The AMF spores were obtained by using a wet filter method and the data obtained were analyzed by descriptive analysis. The results of the study identified that there were 3 genera found, namely Acaulospora sp. Glomus sp and Gigaspora sp. The diversity of FMA species in both locations is classified as moderate. Soil chemical properties correlated with the number and type of arbuscular mycorrhizal spores found at all locations. Further research is needed to clearly identify the species and characteristics of the spores and their application can increase the success of reclamation.